Sex estimation of unidentified human remains: Concordance between morphological anthropological assessment and DNA analysis - Leggett, Celeste Esther (Department of Pathology, 2025)
Identifying skeletonised human remains is a challenge worldwide, and sex determination is an important part of the process. Recently in Cape Town, there have been two medico-legal death investigations involving unidentified skeletonised remains who were estimated to be female anthropologically but were biologically sexed male based on DNA analyses. This study aimed to assess the agreement of sexing methods in a Western Cape South African forensic sample of skeletonised individuals (n=126), who were morphologically estimated to have biological sex as female (n=41). Of the 41 anthropologically estimated to be female cases, 19 were excluded for being probable or likely 'archaeological'. DNA was extracted from hard tissue samples from the remaining 22 individuals and biological sex was assessed by quantitative real-time PCR. DNA from thirteen cases (13/22; 59%) were amplified, with six showing evidence of Y-chromosomal DNA and inferred male sex. However, since the DNA concentrations were below the validated dynamic range, these results were suggestive only. DNA profiling confirmed that one case was male but did not provide further clarity on the biological sex of the remainder of cases due to low copy number (LCN) DNA. This study presents another confirmed case report of sex discordance between anthropological and DNA analysis for a sample of decedents from the Western Cape, South Africa. While qPCR suggested 54% (7/13) agreement and 46% (6/13) disagreement, confirmation in most cases was hindered by LCN DNA. The Western Cape population, influenced by San and Khoe ancestry, tends to have smaller body size and gracility, which may impact the accuracy of morphology-based assessments of male robusticity as they may appear more female or ambiguous. These results highlight the need to update anthropological data for the diverse South African population and implement improved molecular techniques for reliable DNA profiling. This study underscores the limitations of both anthropological and molecular sex methods and stresses the importance of interdisciplinary collaboration for accurate forensic identification.